The actor in costume - Aoife Monks (Palgrave, 2010)
"How do audiences look at an actor in costume onstage? Monks explores this question, engaging with the main theoretical approaches to the study of actors in performance. The book considers costume's power to shape identity and form bodies drawing on examples from Modernist performance to nudity and stage ghosts"--Provided by publisher.